Gender and Religious Authority in Muslim Communities: A SLR on Islamic Education and Multiculturalism - Alwy Ahmed Mohamed; Hanan Zakirah Harun; Usman Aliyu Yunusa (Solo Universal Journal of Islamic Education and Multiculturalism, 2025)
Objective: This study investigates how gender shapes religious authority, leadership, and participation within Muslim communities, with a specific focus on implications for Islamic education and multicultural contexts. The purpose of this research is to systematically analyze how gendered norms influence access to authoritative religious roles and how these norms are being renegotiated across diverse socio-educational settings. Theoretical framework: Grounded in a theoretical framework combining Islamic feminist thought, sociology of religion, and multicultural education, the study conceptualizes religious authority as a socially constructed and interpretive field influenced by power, identity, and knowledge production. Literature review: The literature review highlights three major strands in existing scholarship: (1) gendered hierarchies in traditional religious institutions; (2) emerging forms of women’s authority through educational, digital, and community-based platforms; and (3) multicultural dynamics that reshape gender relations in minority Muslim contexts. Method: Using a Systematic Literature Review (SLR) approach, the study follows PRISMA 2020 guidelines and employs qualitative meta-synthesis to integrate insights from peer-reviewed publications indexed in Scopus, Web of Science, and JSTOR. Studies were selected through transparent inclusion–exclusion criteria and evaluated using the CASP checklist. Thematic analysis was used to interpret patterns across the dataset. Results: The review finds that gender continues to significantly structure religious authority within Muslim communities, particularly through male-dominated leadership traditions and interpretive gatekeeping. However, the results also demonstrate increasing diversification of authority as women, youth, and minority groups gain influence through Islamic educational institutions, online platforms, and multicultural civic spaces. Reformist discourses influenced by Islamic feminism and inclusive pedagogies further contribute to reinterpreting religious texts and expanding gender-inclusive models of leadership. Implications: The study’s implications emphasize the need for Islamic education systems to integrate gender-sensitive pedagogies and support pluralistic interpretations aligned with multicultural realities. Novelty: Its novelty lies in offering the first comprehensive qualitative SLR that synthesizes gender, religious authority, Islamic education, and multiculturalism into a unified analytical lens, providing a broader understanding of shifting power dynamics in contemporary Muslim societies.